Cathodic tandem alkylation/dearomatization of heterocycles enabled by Al-facilitated carbonyl deoxygenation - Jinhui Hu; Weijie Deng; Jianfeng Zhou; Yubing Huang (Nature Communications)
Abstract Developing efficient strategies for the deoxygenative functionalization of carbonyl compounds is crucial for enhancing the effective utilization of biomass and the upgrading of chemical feedstocks. In this study, we present an elegant cathodic reduction strategy that enables a tandem alkylation/dearomatization reaction between quinoline derivatives and aryl aldehydes/ketones in a one-pot process. Our approach can be executed via two distinct paths: the aluminum (Al)-facilitated spin-center shift (SCS) path and the Al-facilitated direct deoxygenation path. Both paths are theoretically substantiated by DFT calculations. The crux of this protocol is the in-situ activation of the alcohol intermediates by Al salts, which substantially lowers the activation energy necessary for the formation of key transition states, thereby effectively facilitating the deoxygenation process. Control experiments have not only successfully identified the intermediates but also established that the hydrogen source for the reaction is derived from water and tetrabutylammonium salt. Notably, this method is transition metal-free and compatible with water and oxygen.